The Bolds to the rescue - Clary, Julian 1959- (Andersen Press, 2016)
The Bolds are a family of hyenas living as humans in a suburban house. But now their kindness to animal waifs and strays has become legendary, and more and more animals keep turning up to stay. Roger the sheep flocks to their house, and Fifi the poodle turns up to learn some new tricks, whilst Sheila the crocodile decides to stay for a while. But when The Bolds take in a couple of race horses who are on the run, they worry their animal magnetism is getting to be too much